The diversity weighted Living Planet Index: controlling for taxonomic bias in a global biodiversity index - McRae,Louise; Deinet,Stefanie; Freeman,Robin (PeerJ Preprints, 2016)
As threats to species continue to increase, we urgently need precise and unbiased measures of the impact these pressures are having on global biodiversity. Some existing indicators of the status and trends of biodiversity largely rely on publicly available data from the scientific and grey literature, and are therefore prone to biases introduced through overrepresentation of well-studied groups and regions in monitoring schemes. This can give misleading estimates of biodiversity trends. Here, we report on an approach to tackle taxonomic and geographic bias in once such indicator (Living Planet Index) by accounting for the estimated number of species within biogeographical realms, and the relative diversity of species within them. Based on a proportionally weighted index, we estimate a global population decline in vertebrate species between 1970 and 2010 of 55% rather than 22% from an index with no proportional weighting. From this dataset, comprising 10,380 populations of 3,038 species from 2,337 data sources, we also find that freshwater populations have declined by 76%, marine populations by 41%, and terrestrial populations by 39% when using proportional weighting (compared to declines of 45%, 2% and 30% respectively). This not only shows starker declines than previously estimated, but suggests that those species for which we have poorer data coverage may be declining more rapidly.
Keywords: biodiversity indicators; biodiversity; ecology; zoology